1980
DOI: 10.1007/bf02408291
|View full text |Cite
|
Sign up to set email alerts
|

Generalization from school to home with autistic children

Abstract: This investigation assessed the generalization of verbal behavior from school to home with three autistic boys. The study attempted to expand upon previous research by Handleman (1979) by analyzing the effects of single versus multiple trainers on generalization. By the use of a multiple-baseline design counterbalanced for treatment condition, the three youngsters were taught responses to common questions in two school settings and were probed to determine transfer of learning to their homes. All three childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As is the case with most of the currently available comprehensive treatment models for children with ASD (Arick et al 2003; Handleman and Harris 2006), the SCERTS model has been theory-based and well operationalized but has yielded limited evidence on the treatment outcomes (Lin et al 2016; Odom et al 2010). Researchers have published manuals that provide detailed guidance for users on how to assess the child, plan and develop appropriate programs, and implement intervention (Prizant et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with most of the currently available comprehensive treatment models for children with ASD (Arick et al 2003; Handleman and Harris 2006), the SCERTS model has been theory-based and well operationalized but has yielded limited evidence on the treatment outcomes (Lin et al 2016; Odom et al 2010). Researchers have published manuals that provide detailed guidance for users on how to assess the child, plan and develop appropriate programs, and implement intervention (Prizant et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The term &dquo;natural environment&dquo; is used here to refer to the various least-restrictive nonschool environments where a variety of tasks will ultimately be performed. Two studies of autistic children demonstrated that school training in varied locations closely resembling home conditions resulted in better generalization to the home than did training in single, dissimilar settings (Handleman, 1979; Handleman & Harris, 1980). Koegel and Rincover (1974) also studied autistic children's generalization of task-readiness skills that were trained in isolate, laboratory settings.…”
Section: Natural Vs Artificial Environmentsmentioning
confidence: 97%
“…Instead, therapeutic efforts have been focused on the children's natural environment, working with the parents at home and ensuring close links between programmes at home and school (Hemsley et al, 1978). In addition, however, it has proved necessary to organize training in such a way as to encourage generalization of learning (Holman and Baer, 1979;Wahler et al, 1979;Handleman and Harris, 1980). Such steps as training in multiple settings; ensuring that cues, stimuli and rewards are comparable across settings; the use of intermittent rather than continuous reinforcement; and an emphasis on the development of self-direction, self-monitoring and the M. y( ?…”
Section: Needmentioning
confidence: 99%